Organizational Culture And Its Importance For The Effectiveness Of Educational Organization And The Psychological Well-Being Of Students - Klyueva, Nadezhda; Ulanova, Galina (Զանգակ հրատ.)
The article is devoted to the influence of the organizational culture of an educational organization on the objective indicators of its effectiveness and the psychological well-being of students in the example of schools in the city of Yaroslavl. A comparative analysis of the effectiveness of educational organizations with a predominance of types of personality and power cultures is presented. The conclusion is made about the existing potential for the formation of the psychological well-being of students in all the presented types of organizational cultures. In the context of these cultures, the authors consider such components of the psychological well-being of students as self-esteem, anxiety, motivation, success and academic success. Differences in the level of satisfaction with the education received among students were revealed depending on the objective indicators of the effectiveness of schools and the prevailing type of organizational culture. The possibilities of positive psychology and resource approach for the formation of psychological well-being at school are indicated.
Keywords: Psychology; Pedagogy